2009
DOI: 10.31018/jans.v1i2.66
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium induced histopathological changes in the stomach and small intestine of Swiss albino mice Mus musculus

Abstract: Abstract:The results on the effect of oral administration of cadmium chloride on the histomorphology of the stomach and small intestine of Swiss albino mice revealed severe histopathological effects in the tissues of both stomach and small intestine. There is marked atrophy of musculature, and disintegration of sub-mucosal and mucosal tissues, distortion of villi with disintegration of mucosal epithelial cells characterized by cytoplasmic vacuolization, nuclear pycnosis and nuclear fragmentation. A significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…In this study, we observed abnormal mucus deposition in the enlarged goblet cells in the intestine of the EDL-treated animals this could be as a result of a proposed mechanism earlier (Zhang and Wang, 1984) [14], that the alteration could be disturbances in lipid inclusions and fat metabolism in response to toxic substances resulting in cytoplasmic vacuolization. This is also similar with an earlier report [15].…”
Section: Discussionsupporting
confidence: 94%
“…In this study, we observed abnormal mucus deposition in the enlarged goblet cells in the intestine of the EDL-treated animals this could be as a result of a proposed mechanism earlier (Zhang and Wang, 1984) [14], that the alteration could be disturbances in lipid inclusions and fat metabolism in response to toxic substances resulting in cytoplasmic vacuolization. This is also similar with an earlier report [15].…”
Section: Discussionsupporting
confidence: 94%